REMOVAL OF LEAD (Pb ) AND ZINC (Zn ) FROM AQUEOUS SOLUTIONS BY ADSORPTION ON VERMICULITE FROM ASKOS AREA IN MACEDONIA (NORTHERN GREECE). - Bourliva, A.; Michailidis, K.; Sikalidis, C.; Trontsios, G. (Bulletin of the Geological Society of Greece, 2004)
The lead and zinc removal from their aqueous solutions by vermiculite samples from Askos area, Northern Greece, was studied using a batch type method. Askos vermiculite is mainly consisted of mixed-layer phyllosilicates. A standard vermiculite sample from Kent, Connecticut was also used for comparison reasons. The concentration of the solutions used varied between 100 and 2000mg/L The maximum uptake capacity of the Askos vermiculite for lead and zinc was found to reach 95% and 96% from solutions containing 100mg/L, respectively. Much lower uptake capacities: 37% for lead and 76% for zinc were found for the Kent vermiculite. The experimental results showed that the Askos vermiculite exhibited an acceptable high capacity for removing metal ions from aqueous solutions. Thus, this untreated and low-cost mineral can find use in purifying heavy metal wastewaters. The uptake distribution coefficient (Kd) showed that the relative lead and zinc removal is higher for initial concentrations below 1000mg/L Batch adsorption experiments conducted at room temperature (22±1°C) showed that the adsorption patterns followed the Freundlich isotherm model. The heavy metal (Pb2+, Zn2+) removal is a rather complicated phenomenon related both to the aqueous chemistry of the elements and the interaction of their cationic species with the used materials. The removal procedure can be attributed to different processes such as ion exchange, adsorption, and precipitation.